2015
DOI: 10.1007/s11103-015-0347-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of the BBX24 promoter and gene from chrysanthemum in Arabidopsis

Abstract: The B-box (BBX) family is a subgroup of zinc finger transcription factors that regulate flowering time, light-regulated morphogenesis, and abiotic stress in Arabidopsis. Overexpression of CmBBX24, a zinc finger transcription factor gene in chrysanthemum, results in abiotic stress tolerance. We have investigated and characterized the promoter of CmBBX24, isolating a 2.7-kb CmBBX24 promoter sequence and annotating a number of abiotic stress-related cis-regulatory elements, such as DRE, MYB, MYC, as well as cis-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…Other authors have also shown the importance of distal promoter regions in stress-associated responses (Behnam et al , 2013; Imtiaz et al , 2015). For example, the 3.0-kb AtNCED3 promoter sequence was able to drive uidA expression in response to dehydration, while the 1.5-kb AtNCED3 promoter region was not functional (Tan et al , 2003; Behnam et al , 2013).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Other authors have also shown the importance of distal promoter regions in stress-associated responses (Behnam et al , 2013; Imtiaz et al , 2015). For example, the 3.0-kb AtNCED3 promoter sequence was able to drive uidA expression in response to dehydration, while the 1.5-kb AtNCED3 promoter region was not functional (Tan et al , 2003; Behnam et al , 2013).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, other constructs containing pGAL -2kb deletions may also be active as drought-responsive, as efficient as the entire sequence. Imtiaz et al (2015) showed that the deletion of the 1,162-bp fragment between −2,552 (full promoter) and −1,390 significantly reduced promoter activity in leaves and roots, while no significant decrease in promoter activity was observed with further deletions from −1,390 to −780, −780 to 600 and −600 to −480. Thus, further analyses will aid in better characterizing the use of the pGAL -2kb promoter as a new drought stress-responsive promoter.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…White chrysanthemum flowers of Hangzhou (WCF‐HZ; Hang Baiju in Chinese) are one of the most popular traditional medicines and food in China. WCF‐HZ can dispel wind and heat, calm the liver, brighten the eyes, and clear heat toxicity . As previously reported, WCF‐HZ mainly contains significant amounts of flavonoids, volatile oils, and hydroxycinnamoylquinic acids, which are considered biologically active components ; WCF‐HZ is used as an important food supplement or herbal tea for antichronic, inflammatory, antihypertensive, abirritative, antispasmodic, antihepatitis B virus, and immunological enhancement activities .…”
Section: Introductionmentioning
confidence: 81%